Flame Spread on an Active Photovoltaic–Roof System - Olaia Aurrekoetxea-Arratibel; Nerea Otano-Aramendi; Daniel Valencia-Caballero; Iñigo Vidaurrazaga; Xabat Oregi; Xabier Olano-Azkune (Fire)
Solar photovoltaic (PV) systems in buildings must comply with both electrotechnical standards for module safety and local building codes, which typically do not address their electrical nature. This regulatory gap creates challenges in assessing the fire performance of PV systems. This paper presents a procedure to adapt a common test method used in some building codes to assess external fire conditions for roofs, while maintaining operative PV modules. Two configurations were tested: an organic PV thin film on a metallic sandwich panel and a glass–glass-encapsulated organic PV module. The tests were conducted under high voltage and current conditions to simulate the systems’ behavior within a larger PV array. Significant electric arcs were observed during testing of the metallic sandwich panel configuration without glass protection when subjected to high voltages or currents. In these cases, total heat release increased by at least 30% compared to non-electrically loaded scenarios or glass-insulated PV modules, likely due to a greater damaged surface area. Electric arcs created new ignition sources, damaging whole PV modules, whereas in the case with no electrical load, propagation flames advanced toward both the upper edge and the corners of the sample, ultimately damaging the entire triangular area above the fire source. The results indicate that the electrical characteristics of PV systems can significantly impact external fire spread behavior. The study identifies challenges in maintaining system activity during testing and simulating real scenarios and proposes for future research directions.